GC-MS Analysis and in vitro Cytotoxicity and Antioxidant Studies on Leucas aspera - Parimaladevi, S.T.; David Raj, C.; Sudha, V.; Brindha, P. (Asian Journal of Chemistry, 2014)
Leucas aspera Spreng. is a common Laminaceous member whose leaf and its juice is traditionally used as medicine for various ailments. The aim of the present work is to prove the antioxidant and cytotoxic efficacy of various parts of Leucas aspera by in vitro methods. Leucas aspera commonly called “Thumbai” is collected from in and around Thanjavur. After proper identification and authentication the different parts of plant were separated and decoction prepared, filtered, lyophilized and subjected to in vitro and chemical studies. The preliminary phytochemical analysis of the test drug revealed the presence of sterols, flavonoids, terpenoids and reducing sugars. GC-MS analysis helped to identify the fragments of the chemical constituents present in the plant. In the present study, antioxidant and cytotoxic efficacy of the selected drug was established through in vitro methods. The efficacy confirmed is further supported by chemical evidences derived from GC-MS analysis.